2016
DOI: 10.5155/eurjchem.7.1.14-18.1331
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibition of carbon steel in chloride solutions by some amino acids

Abstract: The corrosio chloride solu corrosion rate polarization impedance da model to exp The corrosion molecules on remarkably h to depend on process is bas surface. Resul mixed-type in Cite this: Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…This is in accordance with what numerous researchers have observed [19,20]. From Figures (8) and ( 9) and Tables ( 4) and ( 5), it can be seen that the inhibitor concentration of both the sodium nitrate and castor oil is inversely proportional to the carbon steel corrosion rate, given that the higher the inhibitor concentration, the lower the corrosion rate and vice versa.…”
Section: Effect Of Temperature and Rotational Velocity On Dissolution...supporting
confidence: 91%
See 1 more Smart Citation
“…This is in accordance with what numerous researchers have observed [19,20]. From Figures (8) and ( 9) and Tables ( 4) and ( 5), it can be seen that the inhibitor concentration of both the sodium nitrate and castor oil is inversely proportional to the carbon steel corrosion rate, given that the higher the inhibitor concentration, the lower the corrosion rate and vice versa.…”
Section: Effect Of Temperature and Rotational Velocity On Dissolution...supporting
confidence: 91%
“…The idea of corrosion protection with corrosion inhibitors is to produce a thin film on the surface of the material to protect it from corrosion. This is achieved by stimulating it to develop a thick anticorrosive component or by modifying the environmental properties resulting in the prevention or reduction of aggressive behaviour [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the amino acids, El-Sayed NH [62] signaled the corrosion inhibition of carbon steel in stagnant naturally aerated chloride solutions by certain amino acids including glycine, valine, leucine, cysteine, methionine, histidine, threonine, phenylalanine, lysine, proline, aspartic acid, arginine, and glutamic acid using electrochemical techniques. Results showed that all of the amino acids acted as mixed-style inhibitors while cysteine, phenylalanine, arginine, and histidine showed remarkably high corrosion inhibition efficiency at a concentration of 10 mM/dm 3 .…”
Section: Amino Acidsmentioning
confidence: 99%
“…El-Sayed investigated the anti-corrosive effect of some amino acids, such as glycine, valine, leucine, cysteine, methionine, histidine, threonine, phenylalanine, lysine, proline, aspartic acid, arginine, and glutamic acid on carbon steel in stagnant naturally aerated chloride solutions using PP and EIS techniques. All of the amino acids acted as mixed-type inhibitor while cysteine, phenylalanine, arginine, and histidine showed remarkably high corrosion inhibition efficiency at a concentration of 10 mM/dm 3 of functional groups such as OH, SH, or phenyl in the backbone of the amino acid molecules help them undergo better adsorption [62]. Mobin et al studied the inhibitory behavior of mercapto group containing amino acid L-cysteine (CYS) on mild steel in aerated and unstirred 1 M HCl solution using weight loss (WL), PP, and EIS techniques.…”
Section: Amino Acidsmentioning
confidence: 99%